2012
DOI: 10.1007/s11517-012-0862-3
|View full text |Cite
|
Sign up to set email alerts
|

Indirect measurement of pinch and pull forces at the shaft of laparoscopic graspers

Abstract: The grasping instruments used in minimally invasive surgery reduce the ability of the surgeon to feel the forces applied on the tissue, thereby complicating the handling of the tissue and increasing the risk of tissue damage. Force sensors implemented in the forceps of the instruments enable accurate measurements of applied forces, but also complicate the design of the instrument. Alternatively, indirect estimations of tissue interaction forces from measurements of the forces applied on the handle are prone to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…This finding is consistent with previous works related to medical training [11,23,60]. Furthermore, contrary to expected and reported in the literature [31,46], the novice group tends to exert less force than the expert group. This may be due to the location of the force sensing system, representing that the expert group has a more constant and better instrument handgrip, resulting in higher maximum and average force values.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is consistent with previous works related to medical training [11,23,60]. Furthermore, contrary to expected and reported in the literature [31,46], the novice group tends to exert less force than the expert group. This may be due to the location of the force sensing system, representing that the expert group has a more constant and better instrument handgrip, resulting in higher maximum and average force values.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding force measurement, most previous implementations measure forces along the instrument´s shaft [46][47][48][49][50][51], since it transmits the mechanical energy exerted by the surgeon towards the instrument's tip. Other investigators place the sensor at the instrument´s tip [17,24,52], near the handle [36,53,54], or do not focus their sensing system on the instrument, but to another component, such as the trocar [55] or surgeon's gestures [56], keeping the original design of the laparoscopic instruments intact.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between the motor connector angle (θ 1 , θ 2 , θ 3 , θ 4 ) and the Euler angle (α, β, γ) was empirically calculated using Eqs. (3)(4)(5). However, in this paper, because Euler angles were intuitive for surgeons, the roll (α), pitch (β), and yaw (γ) angles can be used instead of da Vinci EndoWrist's connector angle (θ 1 , θ 2 , θ 3 , θ 4 ).…”
Section: Force Measurement With Respect To the Endowrist's Posturementioning
confidence: 99%
“…During the robotic surgery, surgeons do not realize that varying forces are being applied to the endeffector, because the system is an image-guided system; therefore, excessive mechanical force could be applied to cause the breakage of end-effector string ( Fig. 1) or could cause serious tissue injury, such as cutting arteries or nerves [3,10,14,18].…”
Section: Introductionmentioning
confidence: 99%
“…Although the size, sterilizability, biocompatibility, and insulation requirements are more relaxed for the sensors placed outside the body, these locations are more prone to the factors causing sensor inaccuracy. The sensors at the instrument interface, base, and proximal shaft can have the electronics isolated from the patient (Van Den Dobbelsteen et al, 2012). The sensors in the instrument shaft can gain high precision in the lateral direction, but experiments (Lv et al, 2020;Maeda et al, 2016) showed that they do not provide high resolution in the axial direction unless the structure is modified to amplify axial strains.…”
Section: Sensor Locationmentioning
confidence: 99%